Empowering EFL Learners' Communicative Competence through Role-Play in Task-Based Language Teaching (TBLT) - Zulianingrum, Ana (Mozaic : Islam Nusantara, 2025)
This study investigates the role of role-play activities in enhancing vocabulary acquisition and communicative competence among language learners, within the framework of Task-Based Language Teaching (TBLT). The research involved 16 EFL students who participated in role-play scenarios designed to simulate real-life interactions. Data were collected through role-play scripts, classroom observations, and reflective surveys to assess improvements in vocabulary use, pronunciation, fluency, and confidence. The findings reveal that role-play significantly enriches learners' vocabulary, enabling them to effectively use functional language in everyday contexts, such as asking for directions. Learners encountered at least 71 new vocabulary items and utilized 20 expressions for practical communication. Role-play also improved pronunciation and fluency by encouraging spontaneous dialogue and prioritizing communication over grammatical precision. This approach helped reduce anxiety and build learners' confidence in using English, as 90% of participants reported increased confidence in their language skills. The study underscores the pedagogical benefits of role-play in language education, highlighting its alignment with TBLT principles and its effectiveness in preparing learners for real-world communication. Future research should explore the long-term impact of role-play on language proficiency and its applicability across diverse learner demographics. This study contributes valuable insights into the use of role-play as a tool for language acquisition and communicative competence development.